2002
DOI: 10.1111/j.1471-0528.2002.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in pregnant women from a non‐European ethnic minority population—an interventional study

Abstract: In view of the high incidence of subnormal vitamin D levels in women from ethnic minorities, we recommend biochemical screening of these women in early pregnancy, with subsequent supplementation where indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 22 publications
4
47
0
2
Order By: Relevance
“…Previous studies of our group have revealed a rare secondary hyperparathyroidism frequency despite the high incidence of vitamin D deficiency among adolescents in our study population [28,29]. Similarly, Datta et al [21] reported normal PTH levels in 80% of vitamin D-deficient pregnant women. This data affirms that a 25OHD level of 20 ng/ml can be accepted for sufficiency in pregnancy, too.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies of our group have revealed a rare secondary hyperparathyroidism frequency despite the high incidence of vitamin D deficiency among adolescents in our study population [28,29]. Similarly, Datta et al [21] reported normal PTH levels in 80% of vitamin D-deficient pregnant women. This data affirms that a 25OHD level of 20 ng/ml can be accepted for sufficiency in pregnancy, too.…”
Section: Discussionmentioning
confidence: 81%
“…However, previous studies have shown that daily supplementation with 200-600 IU vitamin D is inadequate to obtain sufficient vitamin D status, particularly in high-risk populations. Risk factors for hypovitaminosis D include a high latitude, excessive skin coverage by clothing, low amounts of outdoor activity, and darker skin pigmentation [19,20,21]. Despite the large amount of sunshine in Turkey (Kocaeli, where we conducted this study, has a latitude of 29° N), vitamin D insufficiency/deficiency is very common in this country and region.…”
Section: Discussionmentioning
confidence: 99%
“…A representation of measured prevalence around the world is 8% in Western women in the Netherlands [36], 18% in the United Kingdom [37], 25% in the United Arab Emirates [38], 42% in Northern India [39], 46% in Canada [40], 50% in non-European ethnic minority women in South Wales [41], 59-84% in women with darker pigmentation in the Netherlands [36], 61% in New Zealand [42], 71% in Pakistani women in Norway [43], and 80% in Iran [44]. These studies and others show that high latitude, winter season, dark pigmentation, and full-body skin covering all increase the risk of vitamin D deficiency [35,36,38,39,42,44].…”
Section: Contemporary Maternal Vitamin D Status In Pregnancymentioning
confidence: 99%
“…Des données similaires sont retrouvées chez les femmes enceintes. Des études récentes montrent que 18 % des femmes enceintes en Angleterre, 25 % aux Émirats arabes unis, 80 % en Iran, 42 % au Nord de l'Inde et 60-84 % des femmes non occidentales aux Pays-Bas ont des concentrations en 25OHD inférieures à 25 nmol/l [10][11][12][13][14][15].…”
Section: Abstractsunclassified
“…Dans cette étude, 1 198 primipares ont été étudiées, 4,9 % ont développé une PE. Une concentration sérique en 25OHD inférieure à 37,5 nmol/l, avant 22 SA, était associée à un risque cinq fois plus élevé de développer une PE (OR : 5,0 ; IC 95 % : [1,[7][8][9][10][11][12][13][14]1]) par rapport à une concentration supérieure à 75 nmol/l (indépendamment de l'ethnie, de la saison, du BMI avant la grossesse et de l'âge gestationnel au moment du prélèvement). Depuis un an, trois études observationnelles sont venues renforcer cette hypothèse.…”
Section: Abstractsunclassified